Intelligent Height and Reach Adjustable Electronic Chair for Children with Dwarfism (ZUMP) - R. A., Bakar; Gan, Leong Ming; Wong, Hong Mun; D., Ramasamy; Mohd Fazli, Ismail (Universiti Malaysia Pahang, 2008)
"Dwarfism", "little people", "short statue" or even "midget" are some of the general names given by society to these special communities. According to the definition of the advocacy group for Little People of America (LPA), Dwarfism is a condition characterized by short stature. Technically, an adult with the height of 4 feet 10 inches or under. Based on the study on the dwarfism symptom, it can be caused by any one of more than 200 conditions, most of which are genetic. Most types of dwarfism are known as skeletal dysplasias, which are conditions of abnormal bone growth. In fact, 85% of children with skeletal dyplasias do occur in families where both parents are of average height. Being a dwarfism is not an intellectual disability. A person who has dwarfism is typically of normal intelligence. Somehow, dwarfism is a disease that requires a "cure". Most people with the condition can live long and fulfilling lives. Lastly, it will not be good reason to assume dwarfism is incapable. Little people go to school, go to work, marry, and raise children, just like their average-size peers.